Effect of dietary manganese on antioxidant status and expressions of heat shock proteins and factors in tissues of laying broiler breeders under normal and high environmental temperatures. Issue 11 (28th November 2016) - Zhu, Yong-Wen; Lu, Lin; Li, Wen-Xiang; Zhang, Li-Yang; Ji, Cheng; Lin, Xi; Liu, Hsiao-Ching; Odle, Jack; Luo, Xu-Gang
Abstract: To investigate the effect of Mn on antioxidant status and on the expressions of heat shock proteins/factors in tissues of laying broiler breeders subjected to heat challenge, we used a completely randomised design ( n 6) with a factorial arrangement of 2 environmental temperatures (normal, 21±1°C, and high, 32±1°C)×3 dietary Mn treatments (a Mn-unsupplemented basal diet (CON), or a basal diet supplemented with 120 mg Mn/kg diet, either as inorganic Mn sulphate (iMn) or as organic Mn proteinate (oMn)). There were no interactions ( P >0·10) between environmental temperature and dietary Mn in any of the measured indices. High temperature decreased ( P <0·003) Mn content, and also tended ( P =0·07) to decrease Cu Zn superoxide dismutase (CuZnSOD) activity in the liver and heart. However, an increased Mn superoxide dismutase (MnSOD) activity ( P <0 · 05) and a slight increase in malondialdehyde level ( P =0·06) were detected in breast muscle. Up-regulated ( P <0·05) expressions of heat shock factor 1 ( HSF1 ) and HSF3 mRNA and heat shock protein 70 ( HSP70 ) mRNA and protein were found in all three tissues. Broiler breeders fed either iMn or oMn had higher tissue Mn content ( P <0·0001), heart MnSOD and CuZnSOD activities ( P <0·01) and breast muscle MnSOD protein levels ( P <0·05), and lower ( P <0·05) breast muscle HSP70 mRNA and protein levels compared with those fed CON. Broiler breeders fed oMn had higher ( P <0·03) bone Mn content than those fed iMn. These results indicate that high temperature decreases Mn retention and increases HSP70, HSF1 and HSF3 expressions in the tissues of laying broiler breeders. Furthermore, dietary supplementation with Mn in either source may enhance the heart's antioxidant ability and inhibit the expression of HSP70 in breast muscle. Finally, the organic Mn appears to be more available than inorganic Mn for bone in laying broiler breeders regardless of environmental temperatures.